AUTHENTIC VIDEO: AN ALTERNATIVE TEACHING MATERIAL - Ririn Kurnia Trisnawati (Celt: A Journal of Culture, English Language Teaching & Literature, 2010)
Nowadays, English teachers and lecturers are offered by abundant alternatives for teaching and learning materials. They are so various starting from the traditional ones up to the updates ones. English teaching and learning materials are available from the textbooks, English magazine, newspapers, and others. In addition, Internet is also resource able as the teaching and learning media or material. One way of utilizing Internet as the teaching and learning resource is by downloading some videos from the Internet. Therefore, this paper aims at describing and evaluating the usage of authentic videos for English teaching and learning process. Authentic video is chosen as the material since it could answer the urgency of contextualization, role-modeling, and authenticity in English teaching and learning process which recently becomes the newest interest. Besides, this paper is also to give particular points that authentic videos can also be useful for teaching and learning Grammar/Structure in . It means authentic video is also adaptable to be used in any subjects other than Speaking or Listening.